Case reportHemodynamic support with TandemHeartTM in tako-tsubo cardiomyopathy – a case report - Hassid, Babak; Azmoon, Shah; Aronow, Wilbert; Palaniswamy, Chandrasekar; Cohen, Martin; Gass, Alan (Archives of Medical Science, 2010)
Tako-tsubo cardiomyopathy is characterized by chest pain, electrocardiographic abnormalities mimicking acute myocardial infarction, akinesis or dyskinesis of apical or mid left ventricular segments, and the absence of obstructive coronary artery disease. Tako-tsubo cardiomyopathy is usually a potentially reversible form of cardiac dysfunction. A careful literature search revealed no previous report of a patient requiring mechanical circulatory support in tako-tsubo cardiomyopathy. We report a patient with tako-tsubo cardiomyopathy, ventricular fibrillation, and hemodynamic instability requiring a left ventricular assist device (TandemHeartTM) followed by improvement of left ventricular ejection fraction to 45%.